New breeding objectives for the Czech pig population - KRUPOVÁ, Z; ŽÁKOVÁ, E; KRUPA, E; MICHALIC´KOVÁ, M (The Indian Journal of Animal Sciences, 2017)
The survey was carried out to determine whether the general trends in pig selection schemes are reflected by the local authorised breeders. The number of teats and feed efficiency are expected as new breeding objectives in dam and sire breeds, respectively. Alternatively, some functional traits and sperm quality should be considered for the local pig population. The presented methodology can be widely implicated in other pig populations until the detailed production and economic data for the whole integrated production system is available.